A second-look endoscopy may not reduce the bleeding after endoscopic submucosal dissection for gastric epithelial neoplasm - Takahashi, Fumiaki (BMC Gastroenterol, 2014)
BACKGROUND: Gastric endoscopic submucosal dissection (ESD) has gradually come to be recommended as the optimal treatment for early gastric cancer; however, one of the primary issues is postoperative bleeding. Although second-look endoscopy is conventionally performed to reduce the risk of postoperative bleeding, its benefit has not yet been clearly elucidated. The objective of this study was to elucidate the benefit of second-look endoscopy. METHODS: A total of 459 lesions in patients were underwent gastric ESD from May 2004 to April 2013 at our hospital were included in the analysis. The patients were divided into those who had bleeding within 24 hours after ESD (immediate bleeding) and those in whom bleeding occurred 24 hours or more after the procedure (delayed bleeding); the underlying disease, age, lesion site, diameter of the resected specimen, and lesion diameter were analyzed to identify the risk factors for postoperative bleeding after ESD. RESULTS: Post-ESD immediate or delayed bleeding occurred in 23 of the 459 cases (5.0%). Second-look endoscopy was performed in 210 of 447 cases (47.0%) excluding 12 cases with immediate bleeding; in the remaining 237 of the 447 cases (53.0%), it was not performed. Post-ESD delayed bleeding occurred in 6 of the 210 cases (2.9%) and 5 of the 237 cases (2.1%), with no statistically significant difference between the two groups. Overall, the following factors were identified as the risk factors for postoperative bleeding: young age (P = 0.005), lesions in the L segment (P = 0.042), and large size of the resected specimen (P = 0.005). The risk factors identified in the immediate bleeding group were lesions in the L segment (P = 0.032), large size of the resected specimen (P < 0.001), and large tumor size (P = 0.011), and those in the delayed bleeding group were young age (P = 0.013) and concomitant renal disease (P = 0.011). CONCLUSIONS: The results of this study suggest that second-look endoscopy after gastric ESD may not be useful for preventing postoperative bleeding.